Implementasi Knowledge Management System Berbasis Web untuk Pengelolaan Tata Usaha Menggunakan Model SECI - Yudi Akbar (Jurnal Sains dan Teknologi Informasi, 2026)
The administration of Baburrahim Islamic Boarding School faces various problems in managing organizational knowledge. There is still a lot of knowledge, work experience, and important information owned by employees that has not been well documented. The high rate of employee turnover in the administration section causes the adaptation process of new employees to be less effective. New employees must relearn various work procedures and information from the beginning. The process of sharing knowledge (knowledge sharing) between employees has not run optimally. There is no web-based Knowledge Management System (KMS) available that can be used to store, manage, and distribute knowledge in an integrated manner in the Islamic boarding school environment, with the solution of implementing a Knowledge Management System (KMS) with the SECI method. This system has proven effective in documenting and managing knowledge assets and experiences of staff optimally and has succeeded in achieving the highest standards of effectiveness with a very good predicate focused on strengthening the quality of human resources through optimizing communication channels and accelerating the transfer of insight between personnel. This system plays a strategic role in building a knowledge sharing ecosystem both at the individual and collective levels. This study formulates a KMS model that is adapted to the operational characteristics of the Administration of Baburrahim Islamic Boarding School. By integrating the Soft Systems Methodology (SSM) framework and the SECI model for knowledge conversion, the system design was visualized using the Unified Modeling Language (UML). Functional evaluation conducted through Focus Group Discussions (FGDs) demonstrated excellent validity, while software quality testing achieved the highest effectiveness standards with a very good rating. The final result is a KMS prototype that is effective in documenting employee expertise and serves as a supporting instrument for work performance in the Administration environment